2018
DOI: 10.1111/resp.13246
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and small airway dysfunction in current and former smokers without spirometric COPD

Abstract: Chronic respiratory symptoms are commonly reported by current and former cigarette smokers who lack spirometric evidence of COPD. These individuals are more likely to experience wheezing, breathlessness, limitation in exercise, chronic bronchitis, worse quality of life, exacerbations and more co-morbidities than healthy never-smokers [1][2][3][4] (Fig. 1). The natural history, pathophysiology and management of smokers without evidence of COPD is poorly understood. 3,4 Smoking-induced airway diseases include ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Besides, recent studies showed that exacerbations are frequent in smokers, even they had normal spirometry tests. Another recent study showed that the presence of symptoms in ever-smokers with preserved pulmonary function is correlated with more exacerbations, activity limitation, and greater airway-wall thickening with or without emphysema 28,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, recent studies showed that exacerbations are frequent in smokers, even they had normal spirometry tests. Another recent study showed that the presence of symptoms in ever-smokers with preserved pulmonary function is correlated with more exacerbations, activity limitation, and greater airway-wall thickening with or without emphysema 28,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic bronchitis was associated with peripheral conductive airway function, while wheeze was associated with large airway function. An editorial called for future longitudinal studies that can determine whether MBNW, FOT and high‐resolution computed tomography (CT) scanning can identify smokers at greater risk of developing COPD …”
Section: Copdmentioning
confidence: 99%